Sur l’espace des linéars d’appuis de structure finslériènne - Šinkūnas, J. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Ю. Шинкунас. О пространстве опорных линеаров финслеровой сруктурыJ. Šinkūnas. Apie Finslerio struktūros atraminių linearų erdvę